Pulsed Nd-Yag Laser Deposition Of Diamond-Like Carbon Films - Yap, Seong Shan (2007)
In this work, amorphous, diamond-like carbon (DLG) thin films are readily deposited in high vacuum on substrates, by pulsed Nd:YAG laser ablation of graphite target, which may be placed at two different positions with respect to the forward propagation direction of the ablated carbon plume. A parametric study for obtaining high-quality DLC is carried out with the normal plane deposition.